Model Simulasi Interleaved DC-DC Flyback Untuk Dual Stage Micro-Inverter - Sofitri Rahayu; Sugeng Purwanto; Rudina Okvasari (KILAT, 2022)
DC-DC converter is one of the important parts in the micro-inverter which is used in photovoltaic applications. Its function is to change the output voltage level of 48 Vdc to 5 V dc. The proposed converter topology is flyback because the number of components used is simple so it can reduce production costs and improve ripple voltage. In the flyback converter simulation modeling is done in interleaved mode with maximum output power 12 W using Ltspice software. From the simulation results, it is found that by applying a switching frequency 100 kHz, the value of the primary inductor (Lp) 20 µH, secondary inductor (Ls) 1.5µH, output capacitor (Cout) 100 uF, ripple voltage (VR) 81.02 mV and using IC LT 3758.